Perceived physical accessibility, mother's perception of quality of care, and utilization of skilled delivery service in rural Ethiopia. (July 2021) - Hailemariam, Shewangizaw; Gutema, Lidya; Asnake, Molla; Agegnehu, Wubetu; Endalkachew, Biruk; Molla, Wondwosen
Objective: Despite the concerted effort to improve skilled delivery service utilization in Ethiopia, a considerable proportion of births still occur at home by traditional birth attendants, notably in a rural setting. Hence, the aim of this study was to investigate whether mother's perceived service quality and physical accessibility affect skilled delivery service utilization. Methods: A community-based cross-sectional study was conducted from 1 July 2019 to 30 August 2019, among mothers who gave birth in the last 12 months before the study, in selected five districts of Kaffa Zone, Ethiopia. Result: In this study, 262 (70.1%) of mothers utilized skilled delivery service in their recent childbirth. Mothers regarding the nearby health facility's physical environment as "Good" (adjusted odds ratio = 2.48, 95% confidence interval = 1.44, 4.25), mothers mentioning time to reach to the nearby health facility "<1 h" (adjusted odds ratio = 1.92, 95% confidence interval = 1.11, 3.34), and mothers regarding prompt transport service from home to the nearby health facility "Available" (adjusted odds ratio = 2.01, 95% confidence interval = 1.11, 3.63) were positively associated with skilled delivery services' utilization. Furthermore, completing secondary education and above, attending three and more antenatal care visits, and having good knowledge of danger signs during pregnancy showed a significant association. Conclusion: Although the study evidenced statistically significant association between perceived physical accessibility and perceived service quality, further study is recommended to investigate the relationship between actual physical accessibility and actual service quality. Targeted health education program intended to improve skilled delivery service utilization should give due emphasis on enhancing antenatal care service uptake, and raising mothers' awareness on danger signs during pregnancy, with particular focus on those mothers with low schooling.